KAJIAN REFORMASI ADMINISTRASI PUBLIK UNTUK MEMBANGUN DAYA SAING DAERAH - SARPAN SARPAN (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Public administration reform is an effort that aims to revise, repair, and search for new alternative administration system that is better suited to the development of society and the times today. Since the administrative reforms so inherent in regional autonomy, it is very important to the local government to carry out and manage the regional budget effectively whether it’s from central government or by innovate to increase local revenue. On the other hand, government has a great responsibility to be able to resolve any problems that exist in the regions. Reforms have positive and negative impacts for the government and society, the positive impact that the region has great potential both human and natural resources the region has rapidly grown and developed, but for poor regions will then local natural and human resources are difficult to develop and thrive, even for hire employees will be trouble.